دور الزكاة في مجابهة الآثار الاقتصادية- البطالة- لجائحة كوفيد-19 - بن سيد أحمد, مليكة; يوسفي, رشيد (جامعة الوادي - University of Eloued, 2023)
بعد التفصيل فيما أنجر عن جائحة كوفيد-19،من آثار وخيمة على العالم في جميع ميادين الحياة الاقتصادية والصحية والاجتماعية وعلى مجال العمل والتشغيل في بحثنا هذا، والوصول إلى ضرورة البحث عن السبل الأنجع والبديلة لمواجهة مثل هذه الأزمات، خاصة مع تأكيد الكثير من الدراسات على استمرار هذه الآثار إلى فترة ليست بالهينة (4 سنوات أخرى)، فهدفنا إلى توضيح الدور الرئيسي والفعال للزكاة ومؤسساتها في التصدي لمثل هذه الأزمات إذا ما أعطيت لهذه الشعيرة مكانتها والاستفادة من المؤسسات التي أنشأت في إطارها واستغلالها بشكل فعال ودائم. لنخلص بأن للزكاة أحكاما كثيرة يمكن تفعيلها، كما تحتاج هذه الشريعة لاهتمام أكبر مما توليه الدول الإسلامية خاصة الجزائر، حتى تقوم بالدور المنوط في سد فاقة الفقراء، وتوفير مناصب العمل لمن يحتاج إليها، وتأخذ بيد المفلس لينطلق من جديد After having detailed the serious effects of the Covid-19 pandemic on the whole world and in all areas of economic, health and social life, particularly in the areas of labour and employment, and concluded that there is a need to more effective ways of dealing with such crises. Especially after many studies have confirmed the continuity of these effects for significant periods of time )4 more years.( Therefore, we had to specify the main and effective role of Zakat and its institutions in the management of such crises if this ritual receives its status, as well as the possibility of benefiting from the institutions set up within its framework; and use them effectively and continuously.
The role of the Zakat in conforting the economic effectsunemployment-of the covid-19 pandemic
مقال
Keywords: After having detailed the serious effects of the Covid-19 pandemic on the whole world and in all areas of economic, health and social life, particularly in the areas of labour and employment, and concluded that there is a need to more effective ways of dealing with such crises. Especially after many studies have confirmed the continuity of these effects for significant periods of time )4 more years(. Therefore, we had to specify the main and effective role of Zakat and its institutions in the management of such crises if this ritual receives its status, as well as the possibility of benefiting from the institutions set up within its framework; and use them effectively and continuously. Keywords: COVID-19 pandemic; Pandemic ; unemployment ;Zakat.